Real-time analysis and interpretation of continuous data from structural health monitoring (SHM) systems - Kaya, Yavuz; Safak, Erdal (Bulletin of earthquake engineering, 2015)
The dynamic characteristics of a structure are commonly defined by its modal properties: modal frequencies, damping ratios, and mode shapes. Significant changes in modal properties of a structure after an extreme event, such as an earthquake, or during its service life can be strongly related to damage in the structures. This makes it crucial that the modal properties are accurately estimated and continuously tracked to detect any changes by the structural health monitoring (SHM) system. This paper introduces an algorithm and a MATLAB-based software that includes modules for real-time data processing, modal identification, damage detection, and stakeholder warnings for vibration-based SHM systems. The data processing and modal identification techniques used are based on the classical and stochastic techniques, and utilize running time windows to keep track of time variations in real-time data. The damage detection algorithm makes use of inter-story drifts to detect and locate damage. Since the calculation of inter-story drifts involves double integration and subtraction of acceleration signals, it is extremely hard to get accurate values of inter-story drifts in real-time monitoring. To improve the accuracy, inter-story drifts are calculated for each mode of the structure separately, and then combined synchronously. The displacements at non-instrumented floors are estimated by assuming that the mode shapes can be approximated as a linear combination of those of a shear beam and a bending beam. A software package, REC_MIDS, is developed for this purpose, and it has been operating in a large number of different structures with SHM systems in Turkey (tall buildings, suspension bridges, mosques, museums), and in seven high-rise buildings in UAE.